Spin density and coenzyme M coordination geometry of the ox1 form of methyl-coenzyme M reductase: a pulse EPR study. - Harmer, J; Finazzo, C; Piskorski, R; Bauer, C; Jaun, B; Duin, E; Goenrich, M; Thauer, R; Van Doorslaer, S; Schweiger, A (2005)
Methyl-coenzyme M reductase (MCR) catalyses the reduction of methyl-coenzyme M (CH3-S-CoM) with coenzyme B (H-S-CoB) to CH4 and CoM-S-S-CoB in methanogenic archaea. Here we present a pulse EPR study of the "ready" form MCR(ox1), providing a detailed description of the spin density and the coordination of coenzyme M (CoM) to the Ni cofactor F430. To achieve this, MCR was purified from cells grown in a 61Ni enriched medium and samples were prepared in D2O with the substrate analogue CoM either deuterated in the beta-position or with 33S in the thiol group. To obtain the magnetic parameters ENDOR and HYSCORE measurements were done at X- and Q-band, and CW EPR, at X- and W-band. The hyperfine couplings of the beta-protons of CoM indicate that the nickel to beta-proton distances in MCR(ox1) are very similar to those in Ni(II)-MCR(ox1-silent), and thus the position of CoM relative to F430 is very similar in both species. Our thiolate sulfur and nickel EPR data prove a Ni-S coordination, with an unpaired spin density on the sulfur of 7 +/- 3%. These results highlight the redox-active or noninnocent nature of the sulfur ligand on the oxidation state. Assuming that MCR(ox1) is oxidized relative to the Ni(II) species, the complex is formally best described as a Ni(III) (d7) thiolate in resonance with a thiyl radical/high-spin Ni(II) complex, Ni(III)-(-)SR <--> Ni(II)-*SR.